Management of acute ankle sprain: A literature review - Ketut Kris Adi Marta (Indonesia Journal of Biomedical Science, 2016)
Among musculoskeletal injuries, the incidence of ankle sprains is between 15% and 20% of sports injuries. The ankle is supported laterally by the anterior talofibular ligament, calcaneofibular ligament and posterior talofibular ligament, whilst the medial aspect is supported by the deltoid ligament. Ankle sprains can be either acute sprains, which can be further classified into three grades depending on the severity of the injury, or chronic instability. Acute ankle sprain is usually managed conservatively and functional rehabilitation failure by conservative treatment leads to development of chronic ankle instability, which most often requires surgical intervention. Successful treatment of acute ankle sprain can be achieved with individualized, aggressive and non-operative measures. Surgery should always be indicated on an individual basis